(untitled) (Nexo Revista Científica, 2021)
On sod-podzolic soils, new data is obtained on the functioning of the photosynthetic structures of oat leaves in various climatic conditions and of biomass accumulation (plant productivity). Based on three-year data (2015-2017) of field experiments with 29 oat genotypes, the relationship between the development of productivity elements and the characteristics of the plant assimilation apparatus is analyzed. The pigment content (chlorophyll a, chlorophyll b, carotenoids) was evaluated in acetone extracts on a UVmini-1240 spectrophotometer (SHIMADZU Corporation, Japan). Statistically significant correlations were established between the total leaf surface area and grain mass per plant (r = 0.664), the number of spikelets in a panicle, grain mass per panicle and the mass of the panicle itself (r = 0.548 ... 0.613). These correlations decreased during a drought and increased in conditions of excessive moisture. Oat genotypes with a larger sub-flag leaf had a larger panicle, with a large number of spikelets, grains and of larger grain mass per panicle and plant. During a drought, these correlations decreased. The correlation of the flag leaf area with the grain mass of the panicle and plant under stressful conditions of excessive moisture or a drought increased. With excessive moisture, an increase in the proportion of chlorophyll a in the total chlorophyll pool and in the composition of the reaction centers of photosystems was observed in genotypes with an increased number of spikelets and grains in a panicle, with larger grain masses per panicle and plant, and a mass of 1000 grains. During a drought, the correlation of the content of chlorophylls a and b increased with the following signs: panicle length, panicle mass, number of spikelets in a panicle, and number of grains in a panicle. However, an increase in panicle mass and the number of grains in it was accompanied by a decrease in the proportion of chlorophyll a in the total pigment pool and in the composition of reaction centers.